Side Strain and Impact Injuries at the Iliac Crest Attachment of Lateral Abdominal Wall Musculature in Cricketers: An Uncommon Injury Pattern - Mehta, Chinmay P.; Daftary, Aditya; Lawande, Malini (Indian Journal of Radiology and Imaging, 2021)
Side strains refer to injuries of the internal/external oblique or the transversus abdominis, commonly at their attachment to the lower four ribs and rarely at their pelvic attachments. Injuries at the rib attachments are well-described while literature on iliac crest attachment injuries is sparse. We report four cricketers who had side strain and direct impact injuries with varying degrees of severity at the iliac crest attachment. The purpose of this article is to describe the anatomy, possible mechanism of injury, and imaging findings in the lateral abdominal wall muscle injuries at the iliac crest, which have not been described previously.
Keywords: cricket; iliac crest; MRI; side strain